The Antiviral Drug Valacyclovir Successfully Suppresses Salivary Gland Hypertrophy Virus (SGHV) in Laboratory Colonies of Glossina pallidipes - Abd-Alla, Adly M.M.; Adun, Henry; Parker, Andrew G.; Vreysen, Marc J.B.; Bergoin, Max (PLOS ONE, 2012)
Many species of tsetse flies are infected with a virus that causes salivary gland hypertrophy (SGH) symptoms associated with a reduced fecundity and fertility. A high prevalence of SGH has been correlated with the collapse of two laboratory colonies of Glossina pallidipes and colony maintenance problems in a mass rearing facility in Ethiopia. Mass-production of G. pallidipes is crucial for programs of tsetse control including the sterile insect technique (SIT), and therefore requires a management strategy for this virus. Based on the homology of DNA polymerase between salivary gland hypertrophy virus and herpes viruses at the amino acid level, two antiviral drugs, valacyclovir and acyclovir, classically used against herpes viruses were selected and tested for their toxicity on tsetse flies and their impact on virus replication. While long term per os administration of acyclovir resulted in a significant reduction of productivity of the colonies, no negative effect was observed in colonies fed with valacyclovir-treated blood. Furthermore, treatment of a tsetse colony with valacyclovir for 83 weeks resulted in a significant reduction of viral loads and consequently suppression of SGH symptoms. The combination of initial selection of SGHV-negative flies by non-destructive PCR, a clean feeding system, and valacyclovir treatment resulted in a colony that was free of SGH syndromes in 33 weeks. This is the first report of the use of a drug to control a viral infection in an insect and of the demonstration that valacyclovir can be used to suppress SGH in colonies of G. pallidipes.